DEPENDENCE OF THE DIVINYL YIELD IN THE SYNTHESIS OF DIVINYL FROM ETHYL ALCOHOL ON THE CATALYST COMPOSITION - D. S. Abdimurodova; N. I. Fayzullayev (Innovate Conferences, 2025)
Butadiene-1,3 is an important product in petrochemical synthesis. It is used as a monomer for the production of synthetic rubber and other types of plastics. Butadiene is mainly used in the production of polybutadiene and styrene-butadiene rubbers, which are the main raw materials for the production of automobile tires, mechanical protective coatings, and various types of plastic materials. In 2024, the global production capacity of butadiene exceeded 20 million tons, with an annual growth rate of about 5%. This reflects the high global demand and the important role of butadiene in the petrochemical industry. Currently, the main production technology is to obtain ethylene by pyrolysis of naphtha, with butadiene being obtained as a by-product in this process. Two approaches have been used to study the reduction reaction of crotonaldehyde to 1-hydroxy-2-butylene. The first approach was to attempt the selective reduction of crotonaldehyde with hydrogen using catalysts containing various metals, which have high catalytic activity and yield, and were selected for the process. The second involved the use of ethyl alcohol as a reducing agent, according to the Meyerschein-Ponndorff-Wehrle-Oppenauer reaction.